Bryophytes as regulatory ecosystem services providers in the urban landscape - Kārkliņa, Juta; Kārkliņš, Edgars; Ābele, Lilita; Strazdiņa, Līga (Landscape Architecture and Art, 2025)
Human survival, health and well-being depend directly on ecosystem services or the benefits humans derive from ecosystems. Regulatory ecosystem services are essential to humans as they represent services that regulate the environment, such as climate, clean air and water availability, flood control, etc. Different plants provide ecosystem services in cities, but the authors focus on bryophytes (or mosses) in this article. Moss's ability to provide ecosystem services is represented broadly in the literature, but there is no systematized approach to view them. Therefore, the author's objective of the study is to develop systematization and answer the research question “What ecosystem services provided by mosses to the urban landscape should be included in the systematization of regulating ecosystem services?”. To answer the question, authors fulfilled such tasks as analyzing theoretical sources on the ecosystem services provided by mosses in urban landscapes; to develop a systematization of the regulating ecosystem services and benefits mosses provide to the urban landscape, using systemic analysis. After the execution of the analysis, regulatory ecosystem services provided by mosses were prepared in a systematization depicting interactions and implications. Identified ecosystem services provided by mosses that fulfil regulatory services are: improving air quality, photosynthesis of CO2 into oxygen, rainwater retention, heat island effect reduction, promoting biodiversity, reducing noise pollution, and the long-term impact of climate change. The research rationale is novel in its outcome, as there is a current gap in knowledge of a structured, systematized summary of regulatory ecosystem services provided by mosses. These finding carry both theoretical and practical value, as they can be used both for study purposes and enwidening view on ecosystem services and specific plants providing them; at the same time from practical perspective, this research brings a framework for policy makers, urban planners, and landscape architects on regulatory ecosystem services provided by mosses.